2021
DOI: 10.1038/s41559-021-01616-8
|View full text |Cite
|
Sign up to set email alerts
|

Climatic and soil factors explain the two-dimensional spectrum of global plant trait variation

Abstract: Plant functional traits can predict community assembly and ecosystem functioning and are thus widely used in global models of vegetation dynamics and land–climate feedbacks. Still, we lack a global understanding of how land and climate affect plant traits. A previous global analysis of six traits observed two main axes of variation: (1) size variation at the organ and plant level and (2) leaf economics balancing leaf persistence against plant growth potential. The orthogonality of these two axes suggests they … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
113
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 180 publications
(161 citation statements)
references
References 279 publications
15
113
1
Order By: Relevance
“…Prior research has identified a key set of functional traits that summarize the spectrum of form and function across the plant kingdom, with leaf economics and plant size being the dominant trait axes underpinning life-history strategies 5 , 14 16 . Yet, because such studies have traditionally focused only on a small handful of traits estimated at the species level—often heavily biased towards leaf traits 17 —the full dimensionality of trait space remains unknown. This is particularly problematic for trees, which, due to their size, longevity, ontogeny, and unique structural properties, have distinct characteristics and face novel abiotic stressors relative to herbaceous plants 6 , 13 , 18 21 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Prior research has identified a key set of functional traits that summarize the spectrum of form and function across the plant kingdom, with leaf economics and plant size being the dominant trait axes underpinning life-history strategies 5 , 14 16 . Yet, because such studies have traditionally focused only on a small handful of traits estimated at the species level—often heavily biased towards leaf traits 17 —the full dimensionality of trait space remains unknown. This is particularly problematic for trees, which, due to their size, longevity, ontogeny, and unique structural properties, have distinct characteristics and face novel abiotic stressors relative to herbaceous plants 6 , 13 , 18 21 .…”
Section: Introductionmentioning
confidence: 99%
“…A key limitation when exploring functional trait relationships is the sparsity inherent in most plant trait databases 5 , 17 , 29 , 30 . Such restrictions limit traditional analyses to a small subset of traits and species where there is complete coverage, often capturing only a tiny fraction of known species (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our case, the latter was difficult to implement because the same categorical variables (i.e., woodiness and biogeographical status) would be included in many interaction terms with intercorrelated environmental predictors (Figure S19), which might have led to spurious results (Duncan & Kefford, 2021). Finally, the obtained projections of future trait change were highly uncertain (Figures S8-13), which indicates that other important predictors of trait composition need to be identified and incorporated into further analyses (e.g., soil variables, Joswig et al, 2022). (projected per-cell posterior standard deviations).…”
Section: Study Shortcomingsmentioning
confidence: 99%
“…The adaptation of plants to contrasting gradients of water availability has facilitated major ecological transitions on Earth, such as the migration from exclusively aquatic environments to terrestrial habitats (Rubinstein et al ., 2010; Oliver et al ., 2020), and the subsequent expansions across nearly all land surfaces (Joswig et al ., 2021), of which about half are currently susceptible to droughts (Mishra & Singh, 2010). These worldwide evolutionary adaptations in plants have coexisted for millions of years with strategic associations between plant roots and mycorrhizal fungi (Redecker et al ., 2000; Brundrett & Tedersoo, 2018a; Oliver et al ., 2020), which influence the drought tolerance and survival of extant plant species (Augé, 2001; Lehto & Zwiazek, 2011).…”
Section: Introductionmentioning
confidence: 99%